Crises of Representation, Representations of Crisis: Historical Consciousness in Contemporary Latin American Art and Literature - Thomaz, Daniel Mandur (2013)
The late 1970s and the 1980s were crucial years for the emergence of a new form of historical consciousness in Latin American art and literature, especially concerned with questions of collective memory and identity. The aim of this article is twofold. The first aim is to map the main strands in the debate surrounding the relationships between history, art, and literature in this period, focusing on the current discussions on the epistemological crises that led to the rise of this new historical consciousness. The second aim is to address the question of Latin American specificity. I will take into consideration several theoretical contributions in order to outline a standpoint that not only considers Latin American specificity but also its contribution to think the articulation of art, history and politics.